PERILAKU KNOWLEDGE SHARING PADA PERAWAT RUMAH SAKIT - Muafi . (Journal of Management and Business, 2011)
Nurses have shown on increasing interest in understanding knowledge sharing behaviour in their hospitals. This study uses Ajzen’s theory of planned behavior (TPB) to develop and test a research model to asses the variables that influence encouragement of knowledge sharing intention and behaviour by nurses. The data from a survey shows nurses uses empirically to test the proposed research model. Generally, in the TPB model, the analytical result shows that the research model fit the data well and the main determinants of knowledge sharing behaviour are the encouraging intentions of nurses. Additionally, nurses’ subjective norm and perceived behavioural control are found a positively influence intentions to encourage knowledge sharing. Nurse’s subjective norm is found influence to attitudes positively. An intention to knowledge sharing is found influence to knowledge sharing behavior positively.